Implementation of the Preference Selection Index Method in a Decision Support System for Determining Customer Loan Eligibility - Ilham, Safarul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to apply the Preferential Selection Index (PSI) method in evaluating the eligibility of loan applicants for the PNM Mekaar program. The research investigates the effectiveness of PSI in selecting the most eligible borrowers based on multiple criteria, such as Age, Owns a Business, Loan Capital, Income, Business Permit, Business Permit Level and Customer History. The analysis is conducted using a decision support system (DSS), where each alternative is evaluated against these criteria and weighted accordingly. The study finds that the alternative with the highest value, C8 (0.222403657), is followed closely by alternative A7 (0.207720657). The results of this study demonstrate that PSI offers a more structured, objective, and efficient approach to loan eligibility assessment compared to traditional methods. The integration of PSI within the DSS allows for faster decision-making, improved consistency, and a reduction in the risk of loan defaults. These findings contribute to enhancing the decision-making process in microfinance institutions, particularly in improving financial inclusion and supporting the growth of micro, small, and medium enterprises (MSMEs). The research concludes that PSI is a valuable tool for financial institutions seeking to adopt data-driven, transparent, and reliable loan approval procedures.